Islamic Republic of Iran : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reviews economic developments in the Islamic Republic of Iran during 1990-96. Iran experienced heightened macroeconomic instability in the first quarter of 1995/96. Among the contributing factors, the announcement by the United States of intensification and extension of sanctions had a pronounced negative impact on expectations. This triggered a run on the foreign exchange market and buying in the goods market. The free market exchange rate shot to Rls 6,200 per USD 1 and consumer prices rose by 14 percent during April-May, which raised the 12-month consumer price inflation to 59 percent in May.